Priority Issues In Preparing Youth For Family Life In Uzbekistan - Abirova Umida Nazarovna (Zien Journals, 2025)
The article presents ways and recommendations for improving the social cooperation of families, mahallas, and educational institutions in raising youth in Uzbekistan. The use of innovative technologies in enhancing social cooperation and preparing youth for family life is also highlighted
Keywords: Youth; education; upbringing; family